Sheltered: a thesis exploring the link between bhodrota and the sexual subjectivities of Bangladeshi middle-class new adults - Lateef, Zahra Mayeesha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.